Pediatric and adolescent urologic imaging - Palmer, Jeffrey S.; Palmer, Lane S. (Springer New York, 2014)
Pediatric and Adolescent Urologic Imaging provides a comprehensive reference for health care providers of children and adolescents with urologic conditions. This is the first book in which each chapter is written collaboratively by at least one author from each specialty. This unique approach melds the expertise of each specialist and offers it to the reader in a manner aimed at reinforcing the integration of clinical information to radiologic imaging.      The book is arranged into two sections allowing for easy access to the information. The first section covers the principles of each radiologic modality as well as radiation safety and the history of uroradiology.  The second section integrates the lessons of the first section into specific urologic conditions arranged anatomically and includes additional unique conditions.        Pediatric and Adolescent Urologic Imaging is a key reference for pediatric urologists and radiologists as well as primary care providers, general urologists and radiologists, fellows, residents, medical students, and mid-level providers.